Climate obstruction : how denial, delay and inaction are heating the planet /: how denial, delay and inaction are heating the planet. (2022) - Ekberg, Kristoffer; Forchtner, Bernhard; Hultman, Martin; Jylhä, Kirsti
No abstract available